Relationship between superior-subordinate communication and working relationship: A gender analysis - Abu Bakar, Hassan; Mohamad, Bahtiar (2004)
This research attempts to identify the differences of perceptions between male and female employees on their superior communication behavior. Results of this study reveal that there are different patterns of gender perception for dimensions of superior-subordinate communication behavior.